Population and Habitat Management Development Strategy in The Tapanuli Orangutan (Pongo tapanuliensis) Conservation Area - Perry Muhammad Athoriez, Asep; Samsuri; Purwoko, Agus; Rahmawaty; Rauf, Abdul (Journal of Sylva Indonesiana, 2024)
Tropical forests in Indonesia, which are mega biodiversity countries, have a rich diversity of species, including the Tapanuli orangutan (Pongo tapanuliensis). This species is found in the Batangtoru landscape, mostly in the Other Use Areas (OUA) zone, which can pose a potential threat. The importance of meaningful and long-term local stakeholder engagement. It is necessary to strengthen the management capacity among stakeholders. Therefore, a study of the strategy for developing conservation area management is required. This research aimed to analyze the development and management strategy of conservation areas by related institutions to support the Tapanuli orangutan population and habitat conservation. Despite facing various threats to orangutan conservation, stakeholders still have internal strength. The strategy that must be implemented is to use strength to take advantage of long-term opportunities through a diversification strategy